Cellulose Supported Propylamine/Molybdate Complex: A Novel and Recyclable Nanocatalyst for the Synthesis of Pyranopyrimidine Derivatives - Keshavarz, Raziyeh; Farahi, Mahnaz (Current Organocatalysis, 2022)
Background: Carbon-based materials, due to their unique properties such as lightweight, different forms, doping capability with hetero atoms, low cost, and ease of processability, are suitable support, for heterogeneous catalysts. Among them, cellulose, as one of the most abundant and renewable organic polymers, preserves a key position in many organic raw materials. Pyranopyrimidine derivatives, due to their high biological activity are of interest to both medicinal chemists and biochemists. Moreover, they play the most fundamental structural role in many natural compounds and are medicinally useful molecules. Owing to the great variety of biologically active pyridines, it is not surprising that the pyridine ring system has become a vital basic component in many pharmaceutical agents. Methods: In this study, cellulose as a heterogeneous support was used to prepare an efficient solid catalyst. Cellulose, as the most abundant organic polymer, is a suitable material for this purpose. Then, by immobilizing polyoxomolybdate by a linker on the surface of this carbon-based material, we succeeded in producing Cell@(CH2)3N=Mo[Mo5O18] nanocatalyst. The structure and properties of this catalyst were confirmed by various analyses including FT-IR, XRD, EDS-map, FESEM, and TGA, and its efficacy was evaluated by its use in the preparation of Pyrano[2,3- d]pyrimidine derivatives through a multicomponent reaction between aryl aldehydes, malononitrile, and barbituric acid. Results: The results of this study showed that this new and non-toxic organo-inorganic hybrid nanocatalyst provides the desired products in a short time and with appropriate efficiency. Conclusion: The key features of the present protocol include reusability of the catalyst, ease of recovery, ambient reaction conditions, and simple work-up procedure that make it economic and sustainable.
Keywords: 3-d]pyrimidine